Earthquake performance analysis of a masonry school building's retrofitted state by the equivalent frame method - Okumuş, Vefa; Mangır, Atakan (My University, 2025)
Nonlinear analyses of masonry structures are frequently used in both engineering practice and academic studies. Due to the dominant nonlinear behaviour of masonry structures, complex and extensive finite element models are required to obtain accurate analysis results. While masonry walls are usually modelled using fine-meshed shells or solid elements in such structures, high computing power in modelling, analyzing, and post-processing results is necessary for the analyses of large structures. In recent years, the equivalent frame method, as a solution to this problem has been developed and presented in the literature. In this study, the equivalent frame method is used in a masonry structure modelling, and the axial force-bending relationship is represented by force-based fiber elements. The multi-linear load-deformation relationship reflects the shear behaviour of the walls. Within the scope of the study, an existing masonry school building is modelled using the equivalent frame elements with OpenSees software. Seismic performance analyses are done considering the existing and retrofitted states of the structure, and the results are discussed in a comparative manner.
Keywords: Equivalent Frame Model; Masonry Structures; Opensees; Retrofit; Seismic Performance Analysis